2017
DOI: 10.5194/acp-2017-818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of potential future grand solar minimum for ozone layer and climate

Abstract: Abstract. Continued anthropogenic greenhouse gas (GHG) emissions are expected to cause further global warming throughout the 21 st century. Understanding potential interferences with natural forcings is thus of great interest. Here we investigate the impact of a recently proposed 21 st century grand solar minimum on atmospheric chemistry and climate using the SOCOL3-10 MPIOM chemistry-climate model with interactive ocean. We examine several model simulations for the period 2000 -2199, following the greenhouse … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A new modeling study for the period 2000−2199, investigated the influence on ozone and climate by a hypothetical strong decline in solar activity that would last until 2199. 134 It was found that a reduction of about 15% in solar UV-C radiation would lead to a decrease in ozone production by up to 8%, which would overcompensate the anticipated increase in stratospheric ozone due to reduced stratospheric temperature and acceleration of the BDC. This would lead to a delay in the recovery of total ozone from ODSs, with global ozone not returning to pre-ozone-hole values before the end of the grand solar minimum.…”
Section: Solar Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A new modeling study for the period 2000−2199, investigated the influence on ozone and climate by a hypothetical strong decline in solar activity that would last until 2199. 134 It was found that a reduction of about 15% in solar UV-C radiation would lead to a decrease in ozone production by up to 8%, which would overcompensate the anticipated increase in stratospheric ozone due to reduced stratospheric temperature and acceleration of the BDC. This would lead to a delay in the recovery of total ozone from ODSs, with global ozone not returning to pre-ozone-hole values before the end of the grand solar minimum.…”
Section: Solar Activitymentioning
confidence: 99%
“…135 The effects of changes in high energy electrons due to reduced solar activity have not been fully evaluated yet. 134…”
Section: Solar Activitymentioning
confidence: 99%
“…Besides a change in the relative strengths of the lower and upper branches of the meridional Brewer-Dobson circulation (BDC, Butchart et al, 2006) that resulted in ozone changes (Keeble et al, 2017;Li et al, 2009;Oman et al, 2009), there might be additional reasons for the decline in LSO, including the following: the recent reduction in solar activity (Arsenovic et al, 2018); the influence of halogen-containing very short-lived species and other gases unaccounted for by the MPA (Hossaini et al, 2015;Oman et al, 2016;Oram et al, 2017); increased emissions of inorganic iodine (Cuevas et al, 2018;Karagodin-Doyennel et al, 2021); increased aerosol loading (Andersson et al, 2015); unexpected increase in emissions of trichlorofluoromethane (CFC-11) violating the MPA (Fleming et al, 2020); altitude changes in the extratropical tropopause (Bognar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%